Groundwater quality and the factors that's effecting on its oscillation in the Ishaqi area, using geographic information systems (GIS) - Alibrahimi, Suhaila Najim Abid (Al-Adab Journal, 2020)
The objective of this study is to determine the effect of natural and human factors on the water level of the groundwater and determine the areas of weakness and abundance of this water by relying on modern geographical techniques (GIS) in order to analyze the hydrological characteristics of the groundwater in terms of the number of wells, their location and movement, the factors affecting the change in their level, and the preparation of a special database for this purpose for mapping, Drologih Through the study, which included among the most important results of the following:-The region was affected by tectonic movements that led to distortions in the rock layers that formed the site of the groundwater reservoir in the region-The apparent fluctuation in the water table due to many natural and human factors- To clarify the importance of using modern technologies (GIS) in facilitating the task to reach accurate and rapid results for the development of solutions and appropriate planning for optimal investment and determine the reasons for different using of ground water..